Предмет: Математика,
автор: hvihhvihiihihi
(-7/12)×(-6/7)×(-5/6)×(-4/5)+2/3
Ответы
Автор ответа:
0
Ответ:
(-7/12)×(-6/7)×(-5/6)×(-4/5)+2/3= 1
Автор ответа:
0
Ответ:
1
Пошаговое объяснение:
(-7/12)×(-6/7)×(-5/6)×(-4/5)+2/3 = 1
По действиям:
1. (-7/12) * (-6/7) = 1/2
2. 1/2 * (-5/6) = -5/12
3. -5/12 * (-4/5) = 1/3
4. 1/3 + 2/3 = 1
Похожие вопросы
Предмет: Русский язык,
автор: иппе
Предмет: Русский язык,
автор: ayana033
Предмет: Английский язык,
автор: Moon1231
Предмет: Информатика,
автор: deadtomat1337
Предмет: Геометрия,
автор: rizlpoop